A mixed culture of Propionibacterium freudenreichii and Lactiplantibacillus plantarum as antifungal biopreservatives in bakery product. (June 2022) - Ran, Qiong; Yang, Fan; Geng, Min; Qin, Lujie; Chang, Zhongyi; Gao, Hongliang; Jiang, Deming; Zou, Chunjing; Jia, Caifeng
Abstract: In this study, 15 strains of Lactic acid bacteria (Allata et al.) and 6 strains of propionic acid bacteria (PAB) were firstly tested for their antifungal activity against three spoilage fungi, Aspergillus niger, Penicillium crustosum and Aspergillus flavus . Two strains of LAB and PAB were selected and assessed, alone or paired, for their abilities to inhibit the most resistant mold, Aspergillus niger . A mixed culture of P. freudenreichii D6 and L. plantarum L9 was found to be the most active and their optimal inoculum was 1 × 10 8 and 1 × 10 6  CFU/mL, respectively. Furthermore, the in situ antifungal effect of the mixed culture was evaluated against bakery product spoilage fungi. It was found that the growth of airborne fungi was delayed for up to 7 days. The cell number of L. plantarum L9 was slightly increased by the presence of P. freudenreichii D6. Quantification of three main acids (propionic, lactic and acetic acid) produced by the protective cultures suggested that acetic acid was mainly responsible for the antifungal activity. In conclusion, the mixed culture of P. freudenreichii and L. plantarum may be exploited as biopreservatives in bakery products.